Theoretical Study of the Absorption Refrigeration Cycle Using Water-Lithium Bromide as Working Pair for Cold Storage Application. Issue 1 (March 2020) - Sofyan, Sarwo Edhy; Farhan, Muhammad; Khairil,; Jalaluddin,; Akram,
Abstract: This study aims to investigate the performance of a cooling absorption of the water-lithium bromide cycle for a cold storage application which has a capacity of five tonnes of fish. The cooling absorption system utilizes the waste heat of a 6 MW steam power plant as the heat source for the generator. The thermodynamics analysis is carried out to determine both the heat rejection rate of the power plant and the performance of the refrigeration absorption cycle. The performance of the cooling system is investigated by varying the temperature of each component of the refrigeration absorption cycle (i.e generator, absorber, condenser, and evaporator). Also, the influence of temperature on the heat input (to the generator), heat output (from the absorber), and the pump power, is examined. The results show that the Coefficient of Performance (COP) of the refrigeration absorption system increases when the temperature of the absorber, condenser, and evaporator rises. On the contrary, increasing the temperature of the generator leads to the reduction of the COP of the system. It is also found that the pump power increases when the temperature of the absorber rises, while on the contrary decreases when the generator temperature increases. The results also reveal that the amount of heat input into the generator is directly proportional to the temperature of the generator. While the heat output of the absorber decreases when the temperature of the absorber increases.